1991
DOI: 10.1002/1097-0142(19910501)67:9<2290::aid-cncr2820670914>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

DNA image cytometry. A prognostic tool in squamous cell carcinoma of the esophagus?

Abstract: In 45 patients who underwent an esophagus resection due to a squamous cell carcinoma, in addition to the TNM classification and usual morphologic criteria, the paraffin-embedded material underwent deparaffinization, was rehydrated, and was mechanically and enzymatically processed into a single-cell solution. For evaluating the DNA histogram this was analyzed with the help of automatic single-cell cytophotometric study. The method, contrary to that of flow cytometric study, allows for the selective analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…Numerous studies suggest that DNA aneuploidy is significantly associated with a higher incidence of recurrence 11,22 , 26–28 or poorer patient survival 12,15 , 23,24 , 26–30 . Several studies established DNA aneuploidy as an independent predictor of poor survival using multivariate analysis 21,28 , 31–34 . On the other hand, one study reported that patients with diploid tumours had a poorer survival than those with DNA aneuploid tumours 14 and other authors demonstrate that DNA aneuploidy was not a useful marker in predicting patient survival at all 11,13,16–18,20,25,35,36 …”
Section: Squamous Cell Neoplasiamentioning
confidence: 99%
“…Numerous studies suggest that DNA aneuploidy is significantly associated with a higher incidence of recurrence 11,22 , 26–28 or poorer patient survival 12,15 , 23,24 , 26–30 . Several studies established DNA aneuploidy as an independent predictor of poor survival using multivariate analysis 21,28 , 31–34 . On the other hand, one study reported that patients with diploid tumours had a poorer survival than those with DNA aneuploid tumours 14 and other authors demonstrate that DNA aneuploidy was not a useful marker in predicting patient survival at all 11,13,16–18,20,25,35,36 …”
Section: Squamous Cell Neoplasiamentioning
confidence: 99%
“…Among various variables estimated, such as DNA content, tumor stage and tumor differentiation, only survival was significantly related to the tumor stage. This finding is in discordance with study of Bottger et al 12 . which reported a significant correlation between DNA content of advanced SCC cells and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Ein weiterer objektiver Parameter ist der DNS-Gehalt der Tumorzelle, der vielfach einen Einflul3 auf die Prognose hat [3,4,5]. Bei Tumoren mit numerischen Chromosomenaberrationen, charakterisiert im DNS-Histogramm als aneuploid, haben dabei gegenfiber diploiden Tumoren mit einem normalen Chromosomsatz yon 2 x 23 Chromosomen eine ungiinstigere…”
Section: Diskussionunclassified
“…Flul3zytometrisch ist eine Differenzierung zwischen diploiden Tumorzellen, Entzfindungszellen und Stromagewebe, wie bei der in dieser Untersuchung benutzten Einzelzellzytophotometrie, nicht ohne weiteres m6glich [5]. Nachteil der bildanalytischen DNS-Einzelzellzytophotomettle ist m6glicherweise die nur geringe Anzahl von 120 180 Zellen, die letztendlich zur DNS-Messung herangezogen werden, was abet aufgrund unserer Untersuchung vollkommen ausreichend ist, um den DNS-Gehalt des gesamten Tumors zu bestimmen [3,4]. Die Einzelzellzytophotometrie ist allerdings eine relativ zeitaufwendige und kostenintensive Methode, so dab ein Vergleich mit den routinemfil3ig durchgeffihrten histomorphologischen Parametern durchaus sinnvoll erscheint, um den Stellenwert dieser Methode zu definieren.…”
unclassified
See 1 more Smart Citation